2010
DOI: 10.2174/138945010790030956
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chemotherapy and Radiation in the Treatment of Locally Advanced Non-Small Cell Lung Cancer (NSCLC)

Abstract: Approximately one out of every three patients with non-small cell lung cancer (NSCLC) has locally advanced disease that is surgically unresectable. If their performance status allows, it is current practice to treat these patients with a combination of chemotherapy and external beam irradiation. There have been several studies supporting the addition of chemotherapy to radiation, particularly when delivered concurrently. There is debate over which treatment agents and schedules are most optimal, even with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
(74 reference statements)
0
29
0
Order By: Relevance
“…4,5 Therefore, chemotherapy combined with external beam radiotherapy has played a major role in the management of patients with unresectable lung cancer patients. 6,7 Numerous clinical studies have also confirmed the effectiveness of chemotherapy combined with radiotherapy in the treatment of advanced NSCLC, 8,9 which could prolong survival time and obviously improve the quality of life of patients. 10 However, at present, a great number of patients cannot tolerate the currently available treatment modalities mainly owing to their poor general condition, 11 tumor staging and grading, and severe toxicity after radiotherapy and chemotherapy (myelosuppression, nausea, vomiting, radiation pneumonitis, etc.…”
Section: Introductionmentioning
confidence: 97%
“…4,5 Therefore, chemotherapy combined with external beam radiotherapy has played a major role in the management of patients with unresectable lung cancer patients. 6,7 Numerous clinical studies have also confirmed the effectiveness of chemotherapy combined with radiotherapy in the treatment of advanced NSCLC, 8,9 which could prolong survival time and obviously improve the quality of life of patients. 10 However, at present, a great number of patients cannot tolerate the currently available treatment modalities mainly owing to their poor general condition, 11 tumor staging and grading, and severe toxicity after radiotherapy and chemotherapy (myelosuppression, nausea, vomiting, radiation pneumonitis, etc.…”
Section: Introductionmentioning
confidence: 97%
“…4,5 Therefore, chemotherapy combined with external beam radiotherapy has played a major role in the management of patients with unresectable lung cancer patients. 6,7 Numerous clinical studies have also confirmed the effectiveness of chemotherapy combined with radiotherapy in the treatment of advanced NSCLC, 8,9 which could prolong survival time and obviously improve the quality of life of patients. 10 However, at present, a great number of patients cannot tolerate the currently available treatment modalities mainly owing to their poor general condition, 11 tumor staging and grading, and severe toxicity after radiotherapy and chemotherapy (myelosuppression, nausea, vomiting, radiation pneumonitis, etc.…”
Section: Introductionmentioning
confidence: 98%
“…For patients with stage III NSCLC, treatments are delivered to the patients with a goal of achieving a local tumor control and preventing the systemic metastases 8. Chemotherapy, particularly combined with external beam radiotherapy, can offer some benefits of prolonging overall survival (OS) to the patients with advanced NSCLC 911. However, a large number of patients at an advanced tumor stage are not eligible for the currently available treatment modalities due to their poor general conditions and intolerability to severe toxicities after one or more cycles of first-line chemotherapy, especially the severe adverse events occurring in vital organs 12,13.…”
Section: Introductionmentioning
confidence: 99%